Disociaciones en la interpretación de lo moderno en la ciudad - Córdova-Ramírez, Miguel (2022)
Modernity has interested various intellectuals from various disciplines, including those who are responsible for the design of buildings. However, how was it interpreted to be materialized is perceived as such? The growth of Lima real estate market has promoted the construction of new buildings with the largest offer in the south and southwest areas of the city, these so-called modern buildings are gradually replacing the pre-existing ones. Through a qualitative study, two streets with antagonistic facades in Lince, Jesus Maria and Santa Beatriz neighborhoods were compared to investigate how young adults interpreted this change in the city. It was revealed that their interpretation of modern was dissociated from what promoters put forward and a questioning of modern as a synonymous of progress for the city. It is concluded that building modern buildings does not make a modern city and to improve it, first, it is necessary to question if modernization is necessary.